2024
DOI: 10.1128/mbio.00692-24
|View full text |Cite
|
Sign up to set email alerts
|

Defective viral genomes: advances in understanding their generation, function, and impact on infection outcomes

Justin W. Brennan,
Yan Sun

Abstract: Defective viral genomes (DVGs) are truncated derivatives of their parental viral genomes generated during an aberrant round of viral genomic replication. Distinct classes of DVGs have been identified in most families of both positive- and negative-sense RNA viruses. Importantly, DVGs have been detected in clinical samples from virally infected individuals and an emerging body of association studies implicates DVGs in shaping the severity of disease caused by viral infections in humans. Consequently, there is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 154 publications
0
0
0
Order By: Relevance
“…RNA virus infections frequently produce defective viral genomes, which can influence the course of infection through interactions such as complementation and interference (Dimmock, 2014). Non-clinical studies have extensively associated defective viral genome accumulation with reduced disease severity, while fewer but notable clinical studies have demonstrated this trend in Influenza A (Vasilijevic, 2017) and Respiratory Syncytial Virus (Felt, 2021) infections (Brennan, 2024). Consequently, defective viral genomes have become a recent focus of intense pre-clinical research (Smith, 2016; Meng, 2017; Wasik, 2018; Zhao, 2018; Bdier, 2019; Yamagata, 2019; Tapia, 2019; Harding, 2019), with their antiviral potential holding substantial implications for clinical applications and pandemic preparedness.…”
Section: Introductionmentioning
confidence: 99%
“…RNA virus infections frequently produce defective viral genomes, which can influence the course of infection through interactions such as complementation and interference (Dimmock, 2014). Non-clinical studies have extensively associated defective viral genome accumulation with reduced disease severity, while fewer but notable clinical studies have demonstrated this trend in Influenza A (Vasilijevic, 2017) and Respiratory Syncytial Virus (Felt, 2021) infections (Brennan, 2024). Consequently, defective viral genomes have become a recent focus of intense pre-clinical research (Smith, 2016; Meng, 2017; Wasik, 2018; Zhao, 2018; Bdier, 2019; Yamagata, 2019; Tapia, 2019; Harding, 2019), with their antiviral potential holding substantial implications for clinical applications and pandemic preparedness.…”
Section: Introductionmentioning
confidence: 99%